Functions, diversity, and evolution of traumatic mating. (25th January 2013) - Lange, Rolanda; Reinhardt, Klaus; Michiels, Nico K.; Anthes, Nils
ABSTRACT: Copulation can involve the wounding of the mating partner by specialised devices. This type of mating, which we term traumatic mating, has been regarded as exceptional. Its prevalence, however, has not been compared across taxa, nor have its functions and putative evolutionary pathways. A categorisation has been lacking to date. We here show that traumatic mating is a widespread and diverse phenomenon that likely evolved via several pathways. Its putative functions include: ( i ) anchorage during mating; ( ii ) stimulation of short‐term female reproductive investment; ( iii ) male paternity advantages; and ( iv ) enhanced fertilisation efficiency in transitions to internal fertilisation. Both natural and sexual selection have likely contributed to the parallel evolution of traumatic intromittent organs in phylogenetically distant taxa. These organs are sometimes remarkably similar in shape and often, but not always, inject sperm. The target sites of trauma infliction and the nature of secretions delivered alongside sperm are thus far poorly studied, but data on both are needed to elucidate the function of traumatic mating. The few existing studies that explicitly quantify fitness impacts of traumatic mating indicate that this strategy may often be costly to the party being wounded. However, a comprehensive approach to assess overall investments and returns for both sexes is a major target for future work. Finally, for the first time, we corroborate quantitatively the hypothesis that traumatic mating evolved relatively more often among hermaphroditic than among gonochoric taxa.